EFEKTIVITAS MANAJEMEN PENDIDIKAN DI SEKOLAH ALAM CIOMAS - Sandi Irfanuddin, Muhammad; Nugraha, Acep; Wahyudi, Ahmad (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
This study purpose to determine the effectiveness of education management in Ciomas Natural School. The research method used is descriptive method with a qualitative approach. The process of collecting data in this study through observation, interviews and documentation studies. The results of this study consist of (1) describing managerial activities in the form of all aspects of the scope of education management at the Ciomas Natural School, (2) analyzing the level of effectiveness of education management based on the elements of educational management applied at Ciomas Natural School. Nature school has various benefits for children mentally and creative thinking patterns. Having an atmosphere that is close to nature makes students able to explore the nature around them and make learning more fun. The learning system is supported by the activeness of the teacher in delivering learning materials. Make it easier for students to think critically with the sharing and discussion methods applied at the Ciomas Natural School. Despite all the advantages the school has, the Ciomas Natural School has several drawbacks such as the lack of human resources, library infrastructure that is not yet available, and the lack of parental satisfaction with educational services at the Ciomas Natural School. With these shortcomings, educational management activities are carried out optimally by taking into account all aspects of management elements that run effectively and efficiently.